Epistemology Of Muhammad Iqbal's Existentialism: Its Levation To Islamic Education - Haluti, Rahmat; Munirah, Munirah (Prodi Pendidikan Agama Islam, IAIN Sultan Amai Gorontalo, 2022)
The impoverishment of the philosophical dimension is taking place in this country, and the result, is then the economy becomes the main concern, life is no longer oriented to devoting oneself, guaranteeing the freedom of each individual as well as justice. The results showed that the socio-political and intellectual background of the environment and society influenced a lot of the construction existentialism of Mohammad Iqbal while Soren Kierkegaard was more influenced by the internal conditions of his family and life; Mohammad Iqbal's construction existentialism is destiny, ijtihad, and self-concept, while Soren Aabye Kierkegaard is aesthetic, ethical, and religious; the similarity of the construction of existentialism Mohammad Iqbal and Soren Kierkegaard lies in his similarity in critiques the thought that denies human individuality, Iqbal does a critique of Plato's idealism, while Kierkegaard does a critique of Hegel's idealism, the other similarity is to emphasize the importance of human individuality that demonstrates the true existence of human beings, basing their existential thinking on Existence God; the relevance of the existence of these two figures to Islamic studies is to make aware of the noble identity of man and needs to be maintained so as not to be trapped in materialism and moral impoverishment.